Resonant excitation of Mn local vibrational modes in the higher order Raman spectra of nanocrystalline Ga(1-x)Mn(x)N films - Silva, José Humberto Dias da [UNESP]; Leite, D. M. G. [UNESP]; Zanatta, A. R. (Iop Publishing Ltd, 2008)
The effect of manganese on the vibrational properties of Ga(1-x)Mn(x)N (0 <= x <= 0.18) films has been investigated by Raman scattering using 488.0 and 632.8 nm photon excitations. The first-order transverse and longitudinal optical GaN vibrational bands were observed in the whole composition range using both excitations, while the corresponding overtones, as well as a prominent peak located in 1238 cm(-1) (153.5 meV) were only observed in the Mn-containing films under 488.0 nm excitation. We propose that the peak observed at 1238 cm(-1) is due to resonant Mn local vibrational modes, the excitation process being related to electronic transitions involving the Mn acceptor band.